Complexity and Simplification in Language Shift - Kantarovich, Jessica; Grenoble, Lenore A.; Vinokurova, Antonina; Nesterova, Elena (Frontiers in Communication, 2021)
This paper examines the question of linguistic complexity in two shift ecologies in northeastern Russia. It is frequently claimed that language shift results in linguistic simpliﬁcation across a range of domains in the grammars of shifting speakers (Campbell and Muntzel 1989; Dorian 1989; O’Shannessy 2011). We challenge the breadth of this claim, showing that while there are undoubtedly patterns that can be described as a simpliﬁcation of some grammatical domain, the overall grammars of these speakers cannot be said to be “simple,” as simpliﬁcation in one part of the grammar often corresponds to complexiﬁcation in other parts (“complexity trade-offs”). Furthermore, patterns that are deemed loss or simpliﬁcation are often presented in such a way because they are being compared to earlier varieties of the shifting languages; however, such patterns are entirely typologically expected, are consistent with other languages of the world, and can be seen as more or less complex depending on one’s locus of measurement. In this paper, we present incipient changes taking place in Chukchi (Chukotko-Kamchatkan, ISO ckt) and Even (Tungusic, ISO eve) stemming from the modern language shift context. We evaluate these changes against different notions of complexity to demonstrate that a more nuanced approach to morphosyntactic change in language obsolescence is warranted. While morphological simpliﬁcation is expected in these scenarios, other changes in these speakers’ systems (occurring as potential adaptations in light of simpliﬁcation) provide a more enlightening avenue for research on shifting varieties.